Gadolinium-Enhanced Extracranial MRA Prior to Mechanical Thrombectomy Is Not Associated With an Improved Procedure Speed - Guenego, Adrien; Khoury, Naim; Blanc, Raphaël; Mazighi, Mikael; Smajda, Stanislas; Redjem, Hocine; Ciccio, Gabriele; Desilles, Jean-Philippe; Escalard, Simon; Zuber, Kevin; Chamard, Pauline; Hamdani, Mylène; et al. (Frontiers in Neurology, 2019)
Objectives To assess whether performing a pre-intervention gadolinium-enhanced extracranial magnetic resonance angiogram (MRA) in addition to intracranial vascular imaging is associated with improved thrombectomy time metrics. Methods Consecutive patients treated by MT at a large comprehensive stroke center between January 2012 and December 2017 who were screened using pre-intervention MRI were included. Patients characteristics and procedural data were collected. Univariate and multivariate analysis were performed to compare MT speed, efficacy, complications and clinical outcomes between patients with and without pre-intervention gadolinium-enhanced extracranial MRA. Results A total of 912 patients were treated within the study period, including 288 (31.6%) patients with and 624 (68.4%) patients without extracranial MRA. Multivariate analysis showed no significant difference between groups in groin puncture to clot contact time (RR= 0.93 [0.85-1.02], p=0.14) or to recanalization time (RR= 0.92 [0.83-1.03], p=0.15), rates of successful recanalization (defined as a mTICI 2b or 3, RR= 0.93 [0.62-1.42], p= 0.74), procedural complications (RR= 0.81 [0.51-1.27], p=0.36) and good clinical outcome (defined by a mRS≤2 at 3 months follow-up, RR= 1.05 [0.73-1.52], p= 0.79). Conclusion Performing a pre-intervention gadolinium-enhanced extracranial MRA in addition to non-contrast intracranial MRA at stroke onset does not seem to be associated with a delay or shortening of procedure times.